So cute, I could wait: the effect of cuteness on consumer patience - Wang, Xiaoran; Jiang, Jing; Zhang, Xiadan (Frontiers in Psychology, 2024)
While waiting has been a prevalent and mentally taxing experience for consumers in marketing scenarios, little research has explored situational factors that enhance consumer patience. Drawing on the priming theory, attachment theory, and conservation of resources theory, the current research examines how cuteness as a situational factor affects consumer patience. Across five experiments (N = 1030), we demonstrate that exposure to cuteness enhances consumer patience (Study 1). Moreover, we uncover that the effect is driven by perceived social support employing both mediation (Study 2) and moderation approaches (Study 3). Furthermore, we identify time pressure as the moderator, such that the effect of cuteness on consumer patience only exists among individuals under low time pressure and disappears for those under high time pressure (Study 4). Finally, we examine the downstream consequence of consumer patience for word-of-mouth positivity (Study 5). These findings contribute to the literature on cuteness, patience, and perceived social support, while also offering practical implications for companies seeking to enhance consumer patience.